Influence of biodiesel blends produced in Colombia on a Diesel engine - Mónico Muñoz, Luisa Fernanda; Venegas Pereira, Oscar Hernando (Universiti Malaysai Pahang, 2021)
Diesel engines have dominated the heavy duty and passenger vehicle market in the past 30 years. Consequently, the oil-derived fuels demand and the amount of pollutant emissions have witnessed exponential growth during the last three decades. Although Diesel engines present the advantage of higher efficiency and, therefore, lower levels of CO2 emissions, they produce high levels of NOX and particulate matter. In order to face these difficulties, the use of alternative fuels started booming in the early 2000s and continue to gain influence today. Biodiesel stands out from the alternative fuels’ selection for its ease of use, production, storage and potential to reduce levels of particles, CO, HC and CO2. The main goal of this research is to experimentally determine the influence of palm oil biodiesel produced in Colombia on a Diesel engine’s behavior in terms of engine performance and pollutant emissions. As different mixtures of commercial Diesel and biodiesel at different operating conditions were tested, the results showed that it is possible to maintain the engine’s performance at acceptable levels and to, in some cases, reduce smoke density and NOX levels.

Los motores diésel han dominado el mercado de vehículos pesados y de pasajeros en los últimos 30 años. En consecuencia, la demanda de combustibles derivados del petróleo y la cantidad de emisiones contaminantes han experimentado un crecimiento exponencial durante las tres últimas décadas. Aunque los motores diésel presentan la ventaja de una mayor eficiencia y, por tanto, menores niveles de emisiones de CO2, producen altos niveles de NOX y partículas. Para hacer frente a estas dificultades, el uso de combustibles alternativos empezó a cobrar auge a principios de la década de 2000 y sigue ganando influencia en la actualidad. El biodiésel destaca entre la selección de combustibles alternativos por su facilidad de uso, producción, almacenamiento y potencial para reducir los niveles de partículas, CO, HC y CO2. El objetivo principal de esta investigación es determinar experimentalmente la influencia del biodiesel de aceite de palma producido en Colombia sobre el comportamiento de un motor Diesel en términos de desempeño del motor y emisiones contaminantes. Al ensayar diferentes mezclas de Diesel comercial y biodiesel en diferentes condiciones de operación, los resultados mostraron que es posible mantener el desempeño del motor en niveles aceptables y, en algunos casos, reducir la densidad de humos y los niveles de NOX.
Keywords: Biodiesel; Palm oil; Diesel; Performance; Emissions; Alternative internal; Combustion engine